Frankfurt School, de-colonial thinking and their complementary weaknesses: towards a universalism from the South - Gomes, David (Facultad de Ciencias Políticas y Sociales, 2020)
In this essay I analyze critical thinking, more specifically, some of its limits and possibilities, based on a dialogue between the Frankfurt School and the de-colonial thinking. My hypothesis is that the Frankfurt School studies have an important critical potential that goes beyond the limits of the North; but as long as they are incapable of perceiving the implications of their theoretical ideas beyond the northern borders adequately, these works are unavoidably limited and lack complementation. The recent organization of a great group of authors around the concept of "coloniality" is an alternative that also leads to an important source of critical work of thinking. However, the refusal of all kinds of universality can inadequately limit the de-colonial thinking in some of its strongest features. Thus, I propose the concept of a universalism from the South.